2007
DOI: 10.1126/science.1145432
|View full text |Cite
|
Sign up to set email alerts
|

Light-Responsive Cryptochromes from a Simple Multicellular Animal, the Coral Acropora millepora

Abstract: Hundreds of species of reef-building corals spawn synchronously over a few nights each year, and moonlight regulates this spawning event. However, the molecular elements underpinning the detection of moonlight remain unknown. Here we report the presence of an ancient family of blue-light-sensing photoreceptors, cryptochromes, in the reef-building coral Acropora millepora. In addition to being cryptochrome genes from one of the earliest-diverging eumetazoan phyla, cry1 and cry2 were expressed preferentially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
270
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(293 citation statements)
references
References 19 publications
17
270
5
1
Order By: Relevance
“…Biophysical evidence shows that corals exhibit photoreception in the blue region of the light spectrum [90] and are extraordinarily sensitive to blue spectra matching blue moonlight irradiance levels [91]. Nevertheless, the molecular elements underpinning the detection and response to the low intensity blue moonlight has remained undescribed for many years, and only recently Levy et al [92] reported the presence of an ancient family of bluelight-sensing photoreceptors, cryptochromes (CRYs), in the ubiquitous reef-building coral, Acropora millepora. In addition to being CRYs from the simplest eumetazoan described to date, cry2 gene was expressed preferentially during full versus new Moon nights, suggesting a key role in mass coral spawning.…”
Section: (I) Invertebratesmentioning
confidence: 99%
“…Biophysical evidence shows that corals exhibit photoreception in the blue region of the light spectrum [90] and are extraordinarily sensitive to blue spectra matching blue moonlight irradiance levels [91]. Nevertheless, the molecular elements underpinning the detection and response to the low intensity blue moonlight has remained undescribed for many years, and only recently Levy et al [92] reported the presence of an ancient family of bluelight-sensing photoreceptors, cryptochromes (CRYs), in the ubiquitous reef-building coral, Acropora millepora. In addition to being CRYs from the simplest eumetazoan described to date, cry2 gene was expressed preferentially during full versus new Moon nights, suggesting a key role in mass coral spawning.…”
Section: (I) Invertebratesmentioning
confidence: 99%
“…In contrast to the studies performed with corals [32], the light-induced response in sponges occurs regardless of the spectral range. Since cryptochrome is particularly localized around spicules, it is assumed that skeletal elements operate as waveguides for environmental light that penetrates with significant intensity to water depths of ~20 m in the northern Adriatic Sea, the natural habitat of S. domuncula.…”
Section: The Light-response System In Spongesmentioning
confidence: 39%
“…As in the coral model [32], the expression of poriferan cryptochrome is controlled by light [28]. More specifically, the expression of the S. domuncula cryptochrome gene after light exposure (the light source within the spectral range of 330900 and 700 1100 nm) [29] is primarily restricted to the surface zone of the animal, suggesting that the photoactivated protein is compartmentalized in the cortex (the outer tissue layer).…”
Section: Light Detection System: the Cryptochromementioning
confidence: 97%
See 1 more Smart Citation
“…Proximate causes include reception of environmental signals, endogenous rhythms (sometimes multiple and interacting), endocrinology, physiology, and molecular genetics. Because of such complexity, the general principles of chronobiology have been slow to emerge, although good progress is currently being made in relating cryptochrome photoreception to the rhythmic expression of clock genes (Levy et al 2007;Reitzel et al 2010). The multiplicity of causes of reproductive periodicity is reflected in a great diversity in the resulting patterns of reproduction in marine animals -from mass spawning on only a single date per year (Holland 1981) to continual spawning of some individuals throughout the year (Pearse & Phillips 1968), with almost every intervening possibility (Mercier & Hamel 2009;Takemura et al 2010).…”
Section: Discussionmentioning
confidence: 99%